Incidence of surgical site infections and accompanying risk factors in Algerian patients - Atif, M.L.; Bouadda, N; Bezzaoucha, A; Azouaou, A; Bendali, L; Boubechou, N; Bellouni, R (International Journal of Infection Control, 2007)
In May 2002, the WHO World Health Assembly passed resolution WHA55.18 which urged countries to pay the greatest possible attention to patient safety. The resolution has ensured that the drive for safer health care is becoming a worldwide endeavor, bringing significant benefits to patients in all corners of the globe. In October 2004, WHO launched the World Alliance for Patient Safety (WAPS). The Alliance is concerned with raising awareness and political commitment in relation to improved patient safety. Each year, the Alliance delivers a number of programmes covering systemic and technical aspects to improve patient safety around the world.